Super‐resolution Fluorescence Imaging for Materials Science. Issue 10 (15th August 2017) - Wöll, Dominik; Flors, Cristina
Abstract: While super‐resolution fluorescence imaging has mostly seen applications in the life sciences, an increasing number of laboratories are using these techniques to study materials. This often requires adaptation of the more commonly employed protocols that have been developed for biological systems. Here, the most representative examples of the use of super‐resolution fluorescence microscopy to study a wide range of materials, including polymers, nanofibers, carbon nanostructures, inorganic materials, and other nonbiological systems, are collected. Due to its ability to provide dynamic information, to probe below the outer surface of a material, and to gain information at the molecular level beyond ensemble averaging, super‐resolution fluorescence microscopy has the potential to provide new insights that complement those obtained by well‐established techniques in materials science. Abstract : Super‐resolution fluorescence imaging is spreading beyond biological research and increasingly impacting materials science. Strategies are discussed that have been specifically developed for subdiffraction imaging of materials, and some representative examples of the application of these techniques to polymers, nanofibers, carbon nanostructures, inorganic materials, and other non‐biological systems are reviewed.